SOCIAL MOVEMENT DALAM MENGADVOKASI PRAKTIK FEMALEGENITAL MUTILATION (FGM) DI REPUBLIK GAMBIA - Sa'idatun Nafidah (2020)
This study aims to analyze how social movements carried out by women (feminists) in fighting for women's health rights in the culture of female genital mutilation (FGM) in the Republic of Gambia that violate human rights values. Through social movements, some NGOs put up resistance and advocacy to eliminate the practice. This research uses descriptive methods and qualitative research types. Various elements of society incorporated in NGOs carry out various social activities to make changes in the culture of the people in Gambia which are more dominated by patriarchal culture. The results of social movements encourage the involvement of many international parties to eliminate practices that violate human rights through the rule of law, education, and national and international policies.